The Determinant of Regional Financial Information Transparency on the Official Website of Local Government - Annisa, Rifka; Murtini, Henny (Accounting Analysis Journal, 2018)
This study aims to determine the effect of political competition, local government’s size, local government’s financial independency, audit opinion, and complexity of government to the availability and accessibility of regional financial information (IKD) on the official website of the local government. The measurement of the availability of IKD used component total of LKPD and APBD 2015, while the measurement accessibility of IKD used index of IKD. The population of this study is all of local governments on Java Island that consist of regency government, and district government. The amount of local governments is 119. To collect the data, the writer took 91 local governments from the population as the sample by using Purposive Sampling. The writer also used documentation technique to collect data. Research data analysis uses descriptive analysis statistical and multiple regression analysis with SPSS version 21. The result of this research showed that political competition and audit opinion gives effect to IKD availability on the first research model. The second research model results are political competition and complexity of government gives effect to regional financial information accessibility. The conclusion of this study explain political competition, audit opinion and government complexity affect the availability and accessibility of IKD.